Lethal effect of oxamniquine and praziquantel on mice experimentally infected with Schistosoma mansoni Efeito letal de oxamniquina e praziquantel em camundongos experimentalmente infectados com Schistosoma mansoni - Sonia Maria A.F. Tonelli; Eugênio M.A. Goulart; Edward Tonelli; Paulo Marcos Zech Coelho (Revista do Instituto de Medicina Tropical de São Paulo, 1995)
Lethality caused by administration of oxamniquine and praziquantel to mice infected with Schistosoma mansoni, and their respective controls (uninfected), has been studied. As the results indicate, the infected animals clearly showed higher mortality rates when praziquantel was used. Surprisingly, it may be noted that exactly the contrary occurs in relation to the use of oxamniquine, inasmuch as marked higher mortality rates were seen in the control animals (uninfected). These observations lead to the conclusion that further toxicological studies of antischistosomal drugs using. S. mansoni infected animals are needed. Pesquisou-se a letalidade causada por administração de drogas (oxamniquina e praziquantel) em camundongos infectados por Schistosoma mansoni e seus respectivos controles não infectados. Os resultados indicam que os animais infectados apresentam claramente taxas de mortalidade mais altas, quando foi utilizado o praziquantel. Surpreendentemente, o contrário aconteceu com relação ao uso da oxamniquina, uma vez que taxas de mortalidade marcantemente mais altas puderam ser detectadas nos animais controles (não infectados). Estas observações levam à conclusão de que são necessários mais estudos toxicológicos sobre drogas esquistossomicidas, usandose animais infectados com S. mansoni.